The impact of oxidative balance on all-cause and cause-specific mortality in US adults and cancer survivors: evidence from NHANES 2001–2018 - Juan Wu; Yingdong Han; Menghui Yao; He Zhao; Zhikai Li; Tiange Xie; Yun Zhang; Xuejun Zeng (BMC Cancer)
Abstract Background Oxidative stress is a crucial pathophysiological mechanism in chronic diseases and mortality. While individual oxidative markers have been studied, the comprehensive impact of oxidative balance on mortality risks remains unclear, particularly among cancer survivors. We aimed to investigate the associations of Oxidative Balance Score (OBS) with mortality in both the general population and cancer survivors. Methods This study included 37,317 adults (52% female) from the National Health and Nutrition Examination Survey (2001–2018). OBS was calculated based on antioxidant and pro-oxidant exposures and categorized into quartiles. Survey-weighted Cox proportional hazards models were used to estimate hazard ratios for mortality risks. Restricted cubic spline analyses were performed to examine potential non-linear relationships. Stratified analyses were conducted to further refine the findings. Results During a mean follow-up of 9.1 years, 5,092 deaths occurred. Compared with the lowest quartile, the highest quartile of total OBS was associated with lower risks of all-cause mortality (HR 0.68) and cancer mortality (HR 0.55). Among cancer survivors, similar associations were observed with all-cause mortality (HR 0.66). Component analysis revealed consistent protective effects of antioxidant OBS (HR 0.60 for all-cause mortality), while higher pro-oxidant OBS showed varying associations across mortality causes. Conclusions Higher OBS was associated with lower mortality risks, particularly cancer-related mortality, in both the general population and cancer survivors. While antioxidant exposures showed consistent protective effects, the impact of pro-oxidant exposures varied by mortality causes.